2018
DOI: 10.3389/fphar.2018.00768
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Against MPP+-Induced Cytotoxicity Through the Activation of PI3-K/Akt/GSK3β/MEF2D Signaling Pathway by Rhynchophylline, the Major Tetracyclic Oxindole Alkaloid Isolated From Uncaria rhynchophylla

Abstract: Rhynchophylline is a major tetracyclic oxindole alkaloid in Uncaria rhynchophylla, which has been extensively used as traditional herb medicine for the prevention of convulsions and hypertension. However, there is still little evidence about the neuroprotective effects of rhynchophylline for Parkinson’s disease (PD), a neurodegenerative condition currently without any effective cure. In this present study, the neuroprotective molecular mechanisms of rhynchophylline were investigated in a cellular model associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Akt inhibits GSK-3β function via phosphorylation at serine residue (Ser9 of GSK-3β) and thereby reduces apoptosis (Golpich et al, 2015;Norwitz et al, 2019). In our study, we found that MPTP decreased Akt activity and increased of GSK-3β function, consistent with previous studies (Hu et al, 2018). Remarkably, TA pre-treatment abolished MPTP-induced changes and increased p-Akt/Akt ratio while decreasing GSK-3β activity in mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Akt inhibits GSK-3β function via phosphorylation at serine residue (Ser9 of GSK-3β) and thereby reduces apoptosis (Golpich et al, 2015;Norwitz et al, 2019). In our study, we found that MPTP decreased Akt activity and increased of GSK-3β function, consistent with previous studies (Hu et al, 2018). Remarkably, TA pre-treatment abolished MPTP-induced changes and increased p-Akt/Akt ratio while decreasing GSK-3β activity in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Akt is mainly activated by PI3K, and this pathway promotes cell survival and cytoprotection by phosphorylating various enzymes, including antioxidant proteins and pro-apoptotic regulators, as well as some transcription factors (Nakano et al, 2017;Yue et al, 2017). Inhibition of this cascade is correlated with neurodegeneration, particularly in PD (Hu et al, 2018). GSK-3 is involved in an array of progresses, such as metabolism, gene expression, proliferation and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, all these findings suggest that Uncaria rhynchophylla display neuroprotective action in protecting neuronal damage through multiple pathways which could be due to the beneficial effect of active compounds as well as the combination effect of those compounds present in Uncaria rhynchophylla. Several studies have reported on the neuroprotective effect of alkaloid in Uncaria rhynchophylla such as hirsutine [187], rhynchophylline [188][189][190][191], and isorhynchophylline [192][193][194][195].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…Gastrodin inhibits PDGF-BB induced VSMC migration, its mechanisms may be associated with the inhibition of the JNK signaling pathway activation [ 55 ]. The rhynchophylline can inhibite MPP + -triggered neurotoxicity by stimulating MEF2D via activating PI3-K/Akt/GSK3β signaling pathway [ 56 ].…”
Section: Discussionmentioning
confidence: 99%